Improving the profiling of wheat bacterial and fungal endophytic communities—a PCR clamping approach - Dubois, Benjamin; Delitte, Mathieu; Bragard, Claude; Legrève, Anne; Chandelier, Anne; Debode, Frédéric (Frontiers in Microbiology, 2025)
BackgroundPlant-associated endophytic microbial communities are an important source of biological diversity. To study them, efficient, robust, and standardized characterization methods are necessary. These communities are usually profiled using amplicon high-throughput sequencing (metabarcoding), but the large amount of host DNA often leads to substantial co-amplification of organellar sequences, thereby hampering accurate characterization. A promising solution is the use of PCR clamps, modified oligomers that block non-target DNA amplification. However, no practical guidelines are currently available to support their development, and no sets of clamps enabling comprehensive characterization of endophytic bacterial and fungal communities associated with wheat (Triticum aestivum ssp. aestivum) have been reported.ResultsWe developed PCR clamps to block wheat DNA co-amplification while targeting bacterial or fungal populations. For bacteria, two clamping strategies [blocking primers and peptide nucleic acid (PNA)] were evaluated on the 16S V5V7 region. The PNA exhibited superior efficiency (99.8% bacterial reads), whereas blocking primers still performed well (67–98%) and offered a cheaper alternative. The PNA approach was retained for subsequent designs due to its higher efficiency, and two additional PNAs targeting the 16S V4 region were designed to block chloroplast and mitochondrial DNA, respectively. The best results were achieved using both PNAs simultaneously, with 80% of reads being of bacterial origin. For fungi, two PNA clamps were designed targeting ITS1 and ITS2, leading to a substantial reduction in wheat DNA co-amplification, with up to 94 and 75% fungal reads obtained using the ITS1- and ITS2-targeting PNA, respectively. The results also highlighted that profiling endophytic communities without clamps risks significantly underestimating microbial diversity. Furthermore, four bacterial and fungal mock communities were created as tools for standardization and internal control, confirming that our clamps do not inhibit microbial DNA amplification.ConclusionWhereas amplifications without clamps yielded almost exclusively plant reads, the clamps developed here significantly increased the proportion of microbial reads. This in turn enhanced microbial diversity recovery and the reliability of conclusions drawn from endophytic community analyses. The methodology described provides a framework for clamp development that can be reproduced and adapted to any other host species.